COOPERATIVE RELATIONSHIPS AND FRENCH AND EUROPEAN COMPETITION LAW - Grandvuillemin, Sophie (International Journal of Cooperative Law, 2025)
This article examinesthe confrontation of relations between cooperativesocietiesand their members with competition law.Competition law trivializes cooperative relationships when it comes to protecting the market. Thus, the terms of membership and exclusion, as well as the obligations imposed on cooperative members, are examined byFrench and European anti-competitive practices law, and in particular cartellaw, objectivelyin function of their effectson competition, regardless of the cooperative specificities. On the other hand, cooperative law regains its place when cooperative relationshipsare assessed on a competitive level with regard to the individual situation of members; the French restrictivepractices law («pratiques restrictives») is thus set aside, to preserve the cooperative pact.